Disease modifying effects of simvastatin &/or telmisartan on pulmonary function in patients with mild to moderate chronic obstructive pulmonary disease(COPD) - Hadi, Ali M.; Jaleel Al-Shamma, Kasim; Ali Habeeb, Qais (Journal of the Faculty of Medicine Baghdad, 2012)
Background: chronic obstructive pulmonary disease (COPD) is characterized by chronic airflow limitation and a range of pathological changes in the lung.